Platelets contribute to the initiation of colitis‐associated cancer by promoting immunosuppression. (2nd March 2018) - Servais, L.; Wéra, O.; Dibato Epoh, J.; Delierneux, C.; Bouznad, N.; Rahmouni, S.; Mazzucchelli, G.; Baiwir, D.; Delvenne, P.; Lancellotti, P.; Oury, C.
Abstract : Essentials Inflammation plays a key role in the development of colorectal cancer. Understanding mechanisms of cancer initiation might reveal new anticancer preventive strategy. Hyperactive platelets promote tumor formation by fostering immune evasion of cancer. Platelet inhibition by clopidogrel prevents carcinogenesis by restoring antitumor immunity. Summary: Background: Clinical and experimental evidence support a role for inflammation in the development of colorectal cancer, although the mechanisms are not fully understood. Beyond thrombosis and hemostasis, platelets are key actors in inflammation; they have also been shown to be involved in cancer. However, whether platelets participate in the link between inflammation and cancer is unknown. Objective: To investigate the contribution of platelets and platelet‐derived proteins to inflammation‐elicited colorectal tumor development. Methods: We used a clinically relevant mouse model of colitis‐associated cancer. Platelet secretion and platelet reactivity to thrombin were assessed at each stage of carcinogenesis. We conducted an unbiased proteomic analysis of releasates of platelets isolated at the pretumoral stage to identify soluble factors that might act on tumor development. Plasma levels of the identified proteins were measured during the course of carcinogenesis. We then treated the mice with clopidogrel to efficiently inhibit platelet release reaction. Results: At the pretumoral stage, hyperactive platelets constituted a major source of circulating protumoral serum amyloid A (SAA) proteins. Clopidogrel prevented the early elevation of the plasma SAA protein level, decreased colitis severity, and delayed the formation of dysplastic lesions and adenocarcinoma. Platelet inhibition hindered the expansion and function of immunosuppressive myeloid cells, as well as their infiltration into tumors, but increased the number of tissue CD8 + T cells. Platelets and releasates of platelets from mice with cancer were both able to polarize myeloid cells towards an immunosuppressive phenotype. Conclusions: Thus, platelets promote the initiation of colitis‐associated cancer by enhancing myeloid cell‐dependent immunosuppression. Antiplatelet agents may help to prevent inflammation‐elicited carcinogenesis by restoring antitumor immunity.